Analyzing Simplified BWR Inherent Safety System using IAEA Generic Boiling Water Reactor Simulator - Arby Nuryana; Rida Siti Nur'aini Mahmudah (Universitas Negeri Surabaya, 2021)
The inherent safety of boiling water reactors (BWR) has been a vital research topic in the past decades. This study aimed to observe and analyze the simplified BWR inherent safety system incorporated in IAEA Generic BWR Simulator. This simulator represents important features of BWR and provides graphical information and real-time simulation data. The simulated BWR has 1300 MWe power with ABWR-type containment. To analyze its inherent safety system, three conditions are simulated, i.e., normal condition at 100% power, transient condition (feedwater pumps trip), and emergency condition (loss of coolant accident—LOCA). The simulations were performed for up to 30 minutes since the most critical events in all conditions occurred within that time frame. Sequences of transient and emergency conditions were described in detail with the help of an additional screen recorder and time counting software. Results of several parameters in all simulation conditions were compared and analyzed. It was concluded that the simulator could simulate the normal, transient, and emergency conditions and the simplified version of the BWR inherent safety system.